2016
DOI: 10.3390/ijms17101620
|View full text |Cite
|
Sign up to set email alerts
|

miR33a/miR33b* and miR122 as Possible Contributors to Hepatic Lipid Metabolism in Obese Women with Nonalcoholic Fatty Liver Disease

Abstract: Specific miRNA expression profiles have been shown to be associated with nonalcoholic fatty liver disease (NAFLD). We examined the correlation between the circulating levels and hepatic expression of miR122 and miR33a/b*, the key lipid metabolism-related gene expression and the clinicopathological factors of obese women with NAFLD. We measured miR122 and miR33a/b* expression in liver samples from 62 morbidly obese (MO), 30 moderately obese (ModO), and eight normal-weight controls. MiR122 and miR33a/b* expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 56 publications
4
51
1
Order By: Relevance
“…in various cancers, including liver cancer[ 24 ], abdominal, epithelial cancer, inflammation, diabetes[ 25 ], etc. The microRNAs miR-122, together with miR-133-a, miR-134-a and miR-24, conveniently detectable also in serum and plasma, have recently been reported as biomarkers for hepatic inflammation, contributing to NASH development[ 26 , 27 ]. Similar roles, plus activation in various infections by viruses are reported for IFN Beta[ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…in various cancers, including liver cancer[ 24 ], abdominal, epithelial cancer, inflammation, diabetes[ 25 ], etc. The microRNAs miR-122, together with miR-133-a, miR-134-a and miR-24, conveniently detectable also in serum and plasma, have recently been reported as biomarkers for hepatic inflammation, contributing to NASH development[ 26 , 27 ]. Similar roles, plus activation in various infections by viruses are reported for IFN Beta[ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we showed that lipogenesis seems to be downregulated in advanced stages of simple steatosis [ 4 ], as well as the hepatic lipid metabolism seems to be “controlled” by some miRNAs in patients with NAFLD [ 37 ]. As both the lipid and the iron metabolism seem to be involved in the pathogenesis of NAFLD [ 28 , 32 ], hepcidin seems to have a role in transition from steatosis to NASH [ 23 ] and lipid metabolism might be involved in hepcidin synthesis [ 28 , 32 ], in the present work we aimed to go one step further by exploring the relationship between plasma hepcidin levels, and the presence of NAFLD in morbidly obese patients, and also if any association between the hepatic expression of the main iron and lipid metabolism-related genes exists.…”
Section: Discussionmentioning
confidence: 99%
“…Since Lee et al firstly identified the critical function of miRs in regulating the development of C. elegans [57], mounting lines of evidence have revealed that miRs are pivotal for controlling metabolic homeostasis and represents relevance in diagnosing liver diseases. miR-122, which is the most abundant miRs in the liver, is involved in hepatic cholesterol and lipid metabolism [58], and presented an increased level in circulation in the context of NAFLD [59][60][61][62], making a well predictive panel when combined with miR-29a [29]. Moreover, dysregulated level of circulating miRs were also reported, including miR-122 [29], miR-34a [61,63], miR-33 [62], miR-21 [64], miR-192 [60], miR-221/222 [65], miR-375 [59], and miR-802 [66].…”
Section: Mirs As Markers In Liver Diseasementioning
confidence: 99%